2010
DOI: 10.1117/12.858821
|View full text |Cite
|
Sign up to set email alerts
|

The performance of thin shell adaptive optics for high angular resolution x-ray telescopes

Abstract: The Smart X-ray Optics project is a UK based consortium of five institutions investigating active/adaptive X-ray optics for both large and small scale applications. The large scale application is aimed towards future X-ray telescopes for X-ray astronomy. The work presented here includes the modelling and the testing of the new large scale prototype thin shell optic which incorporates piezoelectric devices to enable the surface to be actively deformed aiming to achieve an angular resolution better than that cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Laser alignment of the mirrors found that the NEMO2 exhibited the smaller focal spot; however, it had a focal length too long to be x-ray tested in the TTF. Consequently, x-ray testing in 2010 was possible for only the NEMO1 26,25 .…”
Section: X-ray Testingmentioning
confidence: 99%
“…Laser alignment of the mirrors found that the NEMO2 exhibited the smaller focal spot; however, it had a focal length too long to be x-ray tested in the TTF. Consequently, x-ray testing in 2010 was possible for only the NEMO1 26,25 .…”
Section: X-ray Testingmentioning
confidence: 99%
“…Chandra is sensitive to x-ray sources 100 times fainter than any previous x-ray telescope, enabled by the high angular resolution (0.5 ) of its four layer mirrors, which are made of microcrystalline glasses coated with irdium (Ir), where the film thickness is about 30 nm. The Chandra observatory is constructed based on the type of Wolter-I, [4,5] its focal length is 10.07 m and it works from 0.2 keV-10 keV. The European Space Agency's x-ray Multi-Mirror Mission [6,7] (XMM-Newton) was launched by Ariane 504 on December 10, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the context of the AHEAD (Integrated Activities in the High-Energy Astrophysics Domain) project, proposed to the European Community in the context of the FP7 funding program and at the time being still under evaluation, it has been proposed to develop a X-ray telescope system prototype formed by of a thin shell segment, which incorporates piezoelectric actuators as an integral part of the thin shells. The final goal is to provide a telescope of several square meters of collecting area and with an angular resolution better than 0.5 arcsec HEW 6 . This could be achieved by adjusting the reflecting surfaces in order to achieve and maintain the high angular resolution.…”
Section: Introductionmentioning
confidence: 99%